Depleting Sandalwood Production and Rising Prices - Rai, S. N.; Sarma, C. R. (Indian Forester, 1990)
Sandal is perhaps the most valuable wood in India. The price of sandal heartwood at the turn of this century used to be Rs. 365/- for a ton which rose to around Rs 80,000/- per ton at present. The production is however depleting very steeply. Sandalwood production and prices of Karnataka and Tamil Nadu are taken up for the study. It is found that the production in Karnataka is decreasing at a rate of 7 per cent per year and increasing slightly from year to year in Tamil Nadu at a rate of 2 per cent. The price of sandalwood is found to increase at a rate of 10 per cent per year per ton. Cause or depletion and remedial measures are given.